Global Trends in Research of Gouty Arthritis Over Past Decade: A Bibliometric Analysis - Deng, Pin; Wang, Shulong; Sun, Xiaojie; Qi, Yinze; Ma, Zhanhua; Pan, Xuyue; Liang, Huan; Wu, Junde; Chen, Zhaojun (Frontiers in Immunology, 2022)
Gouty arthritis (GA), as a multifactorial disease, is characterized by intense pain, active inflammation symptom as well as swollen joints. It has utterly complex pathogenesis, of which the prevalence and incidence rate has increased during the last few decades. To investigate the trends, frontiers, and hot spots in global scientific output in the field of GA research over the last decade, we conducted a bibliometric analysis. We retrieved the Science Citation Index Expanded (SCI-Expanded) of the Web of Science Core Collection (WoSCC) for publications and their record information published from 2012 to 2021. we carried out the bibliometric analysis and visualization analysis of the overall distribution of annual outputs, keywords, active institutions, leading countries, and authors, co-cited references, journals with the VOSviewer and CiteSpace. Using a global citation score (GCS), the impact and quality of papers were assessed. We retrieved 847 articles and reviews in total. In general, the annual number of publications (Np) related to GA research has increased during the latest decade. China published the most papers, and the USA achieved the highest H-index and number of citations (Nc). Assistance Publique Hopitaux Paris and CLINICAL RHEUMATOLOGY are the most productive institutions and periodicals respectively. Paper written by Khanna in 2012 achieved the highest GCS. The most common keywords were “Gout,” “hyperuricemia,” and “gouty arthritis.” This research revealed that though there was a fluctuation in publications related to GA, the NP raised on the whole. China was an enormous creator and the US was an influential nation in this field. The top three contributor creators were Dalbeth N, Wang Y, and Zhou JG. There were few investigations on the treatment of gouty arthritis by Chinese medicine monomer, and "injury," "nlrp3 inflammasome," and "IL-1 beta" were growing research hotspots. Our research illustrated the hotspots of research and trends in the research field of GA during the last decade. Recognition of the most important indicators (researchers, institutes, countries, and journals for the release of GA studies), hotspots in the research field of GA can be helpful for countries, scholars, and policymakers in this field to understand GA better and make decisions.